التحكيم في فض المنازعات المصرفية الإسلامية وامكانية التطبيق في بعض دول الخليج وماليزيا /‏ - ريحان، عبد الرحمن أسعد عبد الرحمن
This research aims at studying the issue of arbitration in Islamic banking disputes. The study tackles the problem of the lack of a clear legal framework for Islamic arbitration institutions that regulates the mechanism of their establishment, and functions. It also tackles a pivotal hypothesis that assumes the lack of a general theoretical framework that used to deal with the process of arbitration positively and effectively, especially in light of the lax of regulation, and the ineffectiveness of the mechanism used in this regard. This had led some Islamic banking institutions to rely on non-Islamic arbitration institutions to settle their banking disputes far away from the injunctions of Islamic Shari'ah, which is something the legitimacy of which is highly controversial. The research relied on several methodologies in solving the problem of the research. The first of which is the historical descriptive methodology, which outlining the concept of arbitration and its historical developments. This was followed by the inductive methodology, surveying the cases where the arbitration contract was used in Islamic banks. Finally, the comparative critical analysis methodology was used in discussing such cases of arbitration, and analyzing them critically and comparatively to uncover the strong points in order to stress their importance, and the weak points to avoid them and offer suggestions to overcome them. The study is divided into a preamble and three parts: the preamble dealt with the history of arbitration before and after the emergence of Islam. The first part of the study dealt with the concept of arbitration, its development, sources in Shari'ah and law, and the evidences of its legitimacy. It also included the definition of arbitration, its sources, philosophy, and development in both Islamic and secular law. The second part of the study consisted of two chapters that dealt with the reality of arbitration and the implications of its contract. As for the third part it discussed arbitration in Islamic banking institutions, and it was divided into two chapters. The first chapter introduced Islamic banking institutions, the laws that established them, and the legal and institutional framework of arbitration, in addition to discussing the issue of settling disputes according to secular law. As for the second chapter it included practical applications on cases of arbitration experienced by Islamic banks, and issues which are related directly to the topic. Moreover, the chapter included a general evaluation of arbitration. The study concluded with a conclusion and a number of findings and recommendations. The most important of such findings is emphasizing the idea that arbitration with an institution that strives to implement Islamic Shari'ah is the sound alternative to settle disputes in the field of Islamic banking. Moreover, the stringency of the legal framework that regulates such arbitration is an essential requirement to ensure the soundness of the arbitration process. As for the recommendations they included the importance of Islamic banking institutions supporting the local and international Islamic arbitration institutions, and preferring them over secular arbitration institutions.